2016
DOI: 10.1111/jocn.13473
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative defecation pattern on postoperative constipation for patients undergoing cardiac surgery

Abstract: During the preoperative period, clinical nurses may evaluate the patients' defecation patterns using valid and reliable scales and follow the defecation of the patients, especially patients with defecation problems, during the postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Preoperative Fiber and Bowel Function defecation patterns leaning toward constipation played a role in postoperative constipation. 7 This finding is also supported in the urogynecology literature in a study by Muñiz et al, 6 which found that surgical patients with preoperative obstructive defecation syndrome were more likely to experience postoperative obstructive defecation-type constipation. Preoperative interventions in these patients may be of benefit and could be an area for future research.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Preoperative Fiber and Bowel Function defecation patterns leaning toward constipation played a role in postoperative constipation. 7 This finding is also supported in the urogynecology literature in a study by Muñiz et al, 6 which found that surgical patients with preoperative obstructive defecation syndrome were more likely to experience postoperative obstructive defecation-type constipation. Preoperative interventions in these patients may be of benefit and could be an area for future research.…”
Section: Discussionmentioning
confidence: 59%
“…Among the women with preexisting constipation, as determined by our constipation score, there was an observed association with a delay in return to BM. A study of cardiac surgery patients also found that preoperative defecation patterns leaning toward constipation played a role in postoperative constipation 7 . This finding is also supported in the urogynecology literature in a study by Muñiz et al, 6 which found that surgical patients with preoperative obstructive defecation syndrome were more likely to experience postoperative obstructive defecation–type constipation.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The system does not currently have a manner to document preadmission bowel patterns experienced by the patient. 6,7,17 Therefore, an assumption must be made that the patient is constipated at the 3-day mark. Unfortunately, this makes it difficult to determine whether the patient's lack of bowel movement is due to opioid therapy or is routine for that patient.…”
Section: Limitationsmentioning
confidence: 99%